Patriotism and Propaganda in First World War Britain : the National War Aims Committee and Civilian Morale - Monger, David (Cambridge : Cambridge University Press, 2013)
This book is the first comprehensive investigation of the British National War Aims Committee during the First World War, providing detailed discussion of the establishment, activities and reception of the British domestic propaganda organisation, together with a careful and extensive analysis of the patriotic content of its propaganda.
Pt. 1. The National War Aims Committee -- pt. 2. Patriotism for a purpose : NWAC propaganda -- pt. 3. The impact of the NWAC.
Title from publishers bibliographic system (viewed on 11 Apr 2014).
Includes bibliographical references and index.
JSTOR
Keywords: Great Britain. -- National War Aims Committee -- History; Great Britain. -- National War Aims Committee; World War, 1914-1918 -- Propaganda; Propaganda, British -- History -- 20th century; Patriotism -- Great Britain -- History -- 20th century; Civilians in war -- Great Britain -- History -- 20th century; Guerre mondiale, 1914-1918 -- Propagande; Propagande britannique -- Histoire -- 20e siècle.; Patriotisme -- Grande-Bretagne -- Histoire -- 20e siècle.; Guerre -- Participation des civils -- Grande-Bretagne -- Histoire -- 20e siècle.; HISTORY -- Military -- World War I; Civilians in war; Patriotism; Propaganda; Propaganda, British; Great Britain; 1900-1999; History